الحقائق الاجتماعية في رواية الأرواح المتمردة - Nurchalis Sofyan (Universitas Islam Negeri Ar-Raniry, 2018)
Lebanon refugees are the most numerous immigrants among other Arab countries. Substantially, the Lebanese immigration occurred in the period of 1860-1914 with a total of approximately 330,000 refugees. Massive immigration is happening to Arab countries, North America, South America, Africa, Australia, and Europe. Historians claim that the cause of the massive immigration is a conflict between religions and political suppression. Researcher wanted to examine other factors that cause immigration, which was written in the novel Al-Arwāḥal-Mutamarridah by Jibrān Khalīl Jibrān, which describes events that took place in Lebanon at that time. So as works of art, the novel also reveals the historical facts. This research led to the conclusion that some expressions in this novel identify the factors that contribute to the Lebanese immigration, which is not revealed in the history books.